2001
DOI: 10.1093/humrep/16.12.2485
|View full text |Cite
|
Sign up to set email alerts
|

Should ICSI be the treatment of choice for all cases of in-vitro conception?

Abstract: There is now considerable discussion whether intracytoplasmic sperm injection (ICSI) should be used in all cases of IVF. A critical and balanced view of the current literature is presented. The difficult question is how to identify men with apparently normal semen who are likely to fail to achieve a pregnancy using IVF. In conclusion, from both the safety and scientific viewpoint, ICSI should only be used in cases where success at IVF is regarded as unlikely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(13 citation statements)
references
References 39 publications
0
11
0
2
Order By: Relevance
“…The fertilization rate for each couple was calculated as the percentage of oocytes fertilized. Fertilization rates were categorized into two groups (≤70% and >70%) and three groups, poor (0-40%), moderate (41-70%), and good (71-100%) [Ola et al 2001]. Similarly, progressive motility was categorized into three groups: poor (0-40%), moderate (41-70%), and good (71-100%) motility [Bonde et al 1998;Tesarik et al 2006].…”
Section: Discussionmentioning
confidence: 99%
“…The fertilization rate for each couple was calculated as the percentage of oocytes fertilized. Fertilization rates were categorized into two groups (≤70% and >70%) and three groups, poor (0-40%), moderate (41-70%), and good (71-100%) [Ola et al 2001]. Similarly, progressive motility was categorized into three groups: poor (0-40%), moderate (41-70%), and good (71-100%) motility [Bonde et al 1998;Tesarik et al 2006].…”
Section: Discussionmentioning
confidence: 99%
“…Taking cost into consideration, ICSI is a more expensive process (Ola et al, 2001). The application of ICSI usually results in more fertilization and available embryos, and therefore more infertile couples have the chance of embryo transfer.…”
Section: Discussionmentioning
confidence: 99%
“…In the ICSI procedure, there is no such selection, and "forced fertilization" can be achieved using spermatozoa that might never have attained natural fertilization. It has been shown that spermatozoa from infertile men have higher rates of defects such as DNA damage [16,17] and aneuploidy [18][19][20], which are likely to have an adverse effect on embryo development [21] and thereby decrease embryo quality. These findings were not true for grade A embryos, probably due to the small sample size.…”
Section: Discussionmentioning
confidence: 99%